1990
DOI: 10.1080/01952307.1990.11735806
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy: Spinal Cord Injury vs. Ambulatory Patients

Abstract: One hundred patients, 35 with spinal cord injury (SCI) and 65 who were ambulatory, underwent percutaneous nephrolithotomy (PNL). Success of complete stone excision, operative morbidity and mortality were compared in the two patient populations. Stone size and complexity were evaluated by X-ray and a single-stage PNL was done using general anesthesia, bi-planar C-arm fluoroscopy, Amplatz renofascial dilators, and two guide wires. Eleven percent of the patients had previously-placed percutaneous nephrostomy tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 10 publications
3
30
0
Order By: Relevance
“…PCNL is the gold standard for stones measuring 2 cm and above in the renal pelvis and this remains the case in patients with SCI. Five published series [26][27][28][29][30] report stone-free rates of around 90%, which at first look appears comparable to the standard PCNL outcomes. (Table 4) However, in the Chicago series all patients had a second-look PCNL as standard, and only 19 renal units were stone free after first PCNL in the UK series.…”
Section: Ureteroscopicmentioning
confidence: 72%
“…PCNL is the gold standard for stones measuring 2 cm and above in the renal pelvis and this remains the case in patients with SCI. Five published series [26][27][28][29][30] report stone-free rates of around 90%, which at first look appears comparable to the standard PCNL outcomes. (Table 4) However, in the Chicago series all patients had a second-look PCNL as standard, and only 19 renal units were stone free after first PCNL in the UK series.…”
Section: Ureteroscopicmentioning
confidence: 72%
“…SCI patients represent a unique group that is associated with multiple co-morbidities, and increased risk of mortality and postoperative complication rate [1][2][3][4][5][6][7][8][9][10][11][12]14]. The most serious urologic complications of SCI and neurogenic bladder dysfunction include the formation of vesicoureteral reflux and hydronephrosis, renal failure, urolithiasis, UTI, bladder cancer, and sexual dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
“…The main factors complicating treatment of urolithiasis in SCI patients include (1) an increased risk of urinary tract infection (UTI) and urosepsis related to neurogenic bladder dysfunction, (2) patient positioning difficulties related to contracture of the extremities, and (3) risks secondary to accompanying co-morbidities. The literature contains a limited number of studies presenting the outcomes of ureteroscopy (URS) [6,7] or percutaneous nephrolithotomy (PNL) [7][8][9][10][11][12] in this specific patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lechevallier et al [13] reported a higher likelihood for renal scar formation after ESWL sessions than after percutaneous nephrolithotomy [13]. Therefore, treatment options were directed towards a percutaneous surgical approach [14][15][16][17], open surgical approach [18], or various combinations of multi-modality treatments [8,19,20]. The decision to perform percutaneous nephrolithotomy in our patient rather than open surgery was influenced by a variety of factors.…”
Section: Discussionmentioning
confidence: 99%